Analysis of the Economic Cycles of Poland in Years 1996–2017 - Pawęta, Bartosz (Journal of Finance and Financial Law, 2018)
Economic fluctuations have always fascinated researches regardless of the approach the took to explain them. It is the human nature to seek for patterns in various areas, economy being one of them. For this the attempt was taken to investigate the impact of the 2008 financial crisis on the economic cycle of Poland. This paper aims at answering whether the morphology before and after the crisis changed and whether they follow theoretical model of classic/modern cycles. The research results clearly show that the pace of growth of the Polish economy has been lower after the crisis. However, Polish economy never faced recession. Because almost all cycles lasted approximately 3.5-4 years, while their morphology was subjected to changes, they can be partly classified as modern cycles. It can be also expected that morphological characteristics of future cycle will be more and more similar to modern ones. The added value of this research is that it clearly shows that the morphological characteristics of the economic cycles in Poland did change in terms of their amplitude in the period analyzed. What is more similar approach can be taken to investigate other economic aggregates. The results might be useful to those in whose interest is future economic performance of Poland.